Effect of Mobile Marketing on Online Purchase Intention in Urban Area - Dahal, Achint; Acharya, Ankur; Shilpakar, Subruto; Risal, Pratham; Narasariya, Aditya; Lawati, Misam Hang (New Perspective: Journal of Business and Economics, 2023)
This study aims to investigate the effect of mobile marketing on the online purchase intentions of Nepalese consumers, particularly in metropolitan areas. The study used non-probability convenience sampling to survey 105 consumers who were targeted by companies using mobile marketing for promotions. The data collected was analyzed using descriptive statistics, correlation, ANOVA, two sample tests, and multiple regression. The findings suggest that mobile marketing alerts, information, trust, and relevance have a significant effect on online purchase intention. The study provides useful insights for marketing and branding strategies. Related research has explored the impact of customer satisfaction with online purchases on website continuance intention (WCI) in Qatar, with a focus on the moderating effect of word-of-mouth (WOM) on the relationship between customer satisfaction and WCI. The study found that online shopping is a vital and interesting activity in the Qatari context, and the findings provide useful insights for future studies to explore the effects of COVID-19 on online purchase intentions. Other research has investigated the impact of product-related and social factors on the purchase intention of smartphone buyers in Nepal, as well as the predictive power of demographic factors on the purchase intention of Kosovar citizens. Overall, the findings of this study suggest that mobile marketing can have a significant impact on online purchase intention among Nepalese consumers. Companies can use mobile marketing alerts, information, trust, and relevance to increase their online sales. However, it is important to consider the specific context and cultural factors when developing marketing and branding strategies. Further research can explore the impact of mobile marketing on online purchase intention in other contexts and investigate the effectiveness of different mobile marketing strategies.